Immediate Effect of Theragun Vs Transcutaneous Electrical Nerve Stimulation in Treating Non-Specific Neck Pain Among Young Adults: Theragun Vs TENS in Treating Non-Specific Neck Pain - Hameed, Fatima; Umair, Muhammad; Kubra, Khadija Tul; Waseem, Syeda Aqsa; Aladal, Saeed (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
The study used Theragun and TENS on non-specific neck pain among young adults. The study was conducted to evaluate the immediate effect of the two modalities for the treatment of non-specific neck pain. Evaluation was made according to the results to determine which treatment is more effective. Objectives: To find out the immediate effects of Theragun vs transcutaneous electrical nerve stimulation (TENS) in treating non-specific neck pain among young adults. Methods: This quasi-experimental study was conducted on 60 young adults with non-specific neck pain, equally divided by gender and assigned to two groups: Group 1 received TENS therapy, and Group 2 received Theragun treatment. Pain was assessed using the Visual Analog Scale (VAS), and cervical range of motion was measured with a universal goniometer pre- and post-intervention. Data were analyzed using SPSS version 22.0. Results: A total of 60 participants were included in the trial of TENS and Theragun, with 30 in each group, equally distributed between males and females. The significance value of Theragun was found to be 0.699 (>0.05), and that of TENS intervention was 0.223 (>0.05). Conclusion: The study concluded that both treatments are effective individually in treating non-specific neck pain, but as a comparative study, there were no significant differences observed.